Geostrategi Indonesia: Menakar Ketahanan Nasional di Tengah Dinamika Global - Arina Najwah Nabillah; Nur Faisah; Zaenul slam (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This article analyzes the urgency of Indonesian Geostrategy, embodied through the concept of National Resilience, in facing increasingly complex global challenges. Using a qualitative-descriptive approach, this article explores the evolution of the geostrategic concept from the time of independence to the digital era, and examines the influence of Astagatra (the five pillars of national resilience) on national stability. The primary focus of this research is to identify contemporary threats such as cyberwarfare, global economic instability, and geopolitical conflicts in the region. The results of the discussion indicate that strengthening the synergy between Tri Gatra (the three pillars of national resilience) and Panca Gatra (the five pillars of national resilience) and adapting an inclusive development strategy are key to maintaining the integrity of the sovereignty of the Unitary State of the Republic of Indonesia (NKRI). This research aims to evaluate the effectiveness of the geostrategic concept in safeguarding the sovereignty of the Unitary State of the Republic of Indonesia), identify the historical transformation of the concept of national resilience, and formulate a development strategy that is adaptive to contemporary threats.